АНТРОПОЦЕНТРИЧЕСКИЕ ПОСЛОВИЦЫ КАК ЭЛЕМЕНТ НАЦИОНАЛЬНОЙ КАРТИНЫ МИРА - Турсунбаев, Б.; Даулетова, М. (SCIENCE and SOCIETY, 2019)
The article analyzes the national features of the proverbs of the Uzbek and Russian languages associated with the customs and traditions of the people, as well as the connection of anthropocentric proverbs with the culture of the people.